Design of Natural Convection Solar Dryer for Coffee Beans with Monitoring System Based on Internet of Things - Nurdin Nurdin; Irwin Syahri Cebro; Azhar Azhar; Hendrawati Hendrawati (Jurnal POLIMESIN, 2022)
The process of monitoring the drying of coffee beans so far is still done traditionally so that the effectiveness of the drying process is still low. The IoT-based drying monitoring process is expected to provide better effectiveness and time efficiency. This research designs and manufactures a solar dryer with natural convection heat transfer for coffee beans equipped with an Internet of Things-based monitoring system. The purpose of this study is to develop the performance of a solar dryer with natural convection with the addition of an IoT-based monitoring unit. The research begins with a technical plan for the main components of the dryer. Components whose shapes, dimensions, and materials have been planned will be outlined in the form of detailed technical drawings. Detailed technical drawings will be a guide in the dryer manufacturing process. The main components of the dryer are solar collectors, drying chambers, and an IoT-based monitoring system. The solar collector will function to capture heat from the sun which will flow naturally into the drying room. An IoT-based monitoring system will capture the temperature and humidity (DFRobot DHT22 sensor) in the solar collector, drying room, and the environment of the dryer. In addition, a Bh1750 sensor to capture the intensity of the sun is also embedded in this monitoring system. This monitoring system will be connected to the internet network where the data will be sent to a cloud data server. The recorded data can then be downloaded using a mobile device or personal computer connected to the internet network. This IoT-based monitoring system was chosen so that performance data from the dryer can be monitored in real-time and online. The results of this study are a prototype dryer with a household capacity of 9 Kg equipped with an IoT-based monitoring system has been built and can be implemented properly